Changing organisational culture: another role for self-advocacy?. Issue 2 (7th April 2015) - Miller, Robin
Abstract : Purpose: – Improvements in organisational culture are a common recommendation of enquiries into system failure and an aspiration of policy. The purpose of this paper is to explore an initiative to change culture in a low-secure service through the introduction of a self-advocacy group. Design/methodology/approach: – An independent evaluation was carried out by a university research team. A theory-based methodology was deployed with qualitative data gathered through observations, interviews and focus groups. Findings: – Culture change was reported by senior managers and clinicians in relation to the transparency of the service, decision making regarding resources, and engagement of patients in redesign. Self-advocacy group members reported a different relationship with senior management which in turn enabled greater influence in the organisation. Achieving these impacts relied on independent and skilled external facilitation, support from senior managers, and a calm and democratic atmosphere in the meetings. Ward staff were kept at an arms-length from the group and were less certain that it had made any difference to the way in which the ward operated. Research limitations/implications: – The research was only based in one organisation and the impacts of the initiative may vary with a different local context. Research in a wider sample of organisations and culture change initiatives will provide greater insights. Practical implications: – Self-advocacy groups can lead to organisation culture change alongside benefits for individual group members but require funding, external and independent facilitation, and organisational endorsement and support. Originality/value: – This paper adds to the limited literature regarding culture change in secure services and services for people with a learning disability in general and also to the understanding of the impact of self-advocacy groups.